2023
DOI: 10.21203/rs.3.rs-2466807/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ZWINT is a cancer prognosis and immune infiltration-related biomarker from pan-cancer analysis

Abstract: ZWINT plays an important role in regulating the mitotic checkpoint and cell cycle, and is closely associated with tumor proliferation and migration. Recent studies have shown that high ZWINT expression is associated with poor prognosis in patients with lung adenocarcinoma(LUAD) and Glioblastoma (GBM). Previous analyses of ZWINT were limited to a certain type of cancer, but there has not been a systematic pan-cancer study of ZWINT. We used the TCGA (The Cancer Genome Atlas) project and GTEx data (Genotype-Tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…ZWINT is a crucial constituent of the mitotic spindle checkpoint, which plays a pivotal role in ensuring accurate chromosome segregation during cell division and maintaining genomic stability. [14,15] Recent studies have shown that ZWINT may be involved in the pathogenesis of tumour development and is overexpressed in a variety of malignancies including colon, breast, liver, lung and pancreatic cancers [8,[16][17][18][19][20][21] .However, the regulation of ZWINT in ovarian cancer and its molecular mechanism have not been reported yet. The results of this study showed that ZWINT was significantly highly expressed in ovarian cancer tissues, the higher the expression level of ZWINT, the worse the overall survival and disease-free survival of the patients, which indicates that ZWINT is closely related to the development of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…ZWINT is a crucial constituent of the mitotic spindle checkpoint, which plays a pivotal role in ensuring accurate chromosome segregation during cell division and maintaining genomic stability. [14,15] Recent studies have shown that ZWINT may be involved in the pathogenesis of tumour development and is overexpressed in a variety of malignancies including colon, breast, liver, lung and pancreatic cancers [8,[16][17][18][19][20][21] .However, the regulation of ZWINT in ovarian cancer and its molecular mechanism have not been reported yet. The results of this study showed that ZWINT was significantly highly expressed in ovarian cancer tissues, the higher the expression level of ZWINT, the worse the overall survival and disease-free survival of the patients, which indicates that ZWINT is closely related to the development of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%